TADS: An assessment methodology for agile supply chains - M. Balaji (Journal of Applied Research and Technology, 2015)
Globalization has been facilitating the entry of numerous competitors in the world of manufacturing market. As a result, modern manufacturers are approached by numerous players in the market to provide varieties of products. To achieve competitive edge in the rapidly changing business environment, organizations must align with suppliers and customers to streamline operations and work together to achieve desired levels of agility. In a bid to cope with market instability, companies now look beyond cost advantage. Speed, quality and agility are being emphasized as means of responding to the unique needs of customers and markets. This study deals with improving the flexibility levels of the supply chain of an organization by analyzing various agility criteria and calculating the agility index. This is a distinguished effort in creating agile supply chains using Total Agile Design Systems as an assessment tool.